"Cat-gras" delusion: a unique misidentification syndrome and a novel explanation. Issue 2 (3rd March 2016) - Darby, R. Ryan; Caplan, David
ABSRACT: Capgras syndrome is a distressing delusion found in a variety of neurological and psychiatric diseases where a patient believes that a family member, friend, or loved one has been replaced by an imposter. Patients recognize the physical resemblance of a familiar acquaintance but feel that the identity of that person is no longer the same. Here we describe a 73-year-old male with right posterior frontal and bilateral anterior-medial frontal damage from prior brain trauma with a similar delusion of an imposter replacing his pet cat. Misidentification syndromes for animals, as opposed to humans, have been rarely reported. Neuropsychological testing showed deficits in executive processing and memory retrieval with prominent intrusions and false positive responses. The delusional belief content in Capgras syndrome has been hypothesized to result from loss of an emotional or autonomic response to familiar stimuli, from theory of mind deficits, or from loss of self-environment distinctions. We instead propose that Capgras delusions result from a dysfunction in linking external stimuli with retrieved internal autobiographical memories pertaining to that object. This leads to an erroneously learned identity that persists as a specific delusional belief.